2011
DOI: 10.1007/s11433-011-4429-3
|View full text |Cite
|
Sign up to set email alerts
|

Description of squeezed surface plasmons

Abstract: Surface plasmon polaritons (SPPs) are the combined electron oscillations and electromagnetic waves propagating along the interface between a conductor and a dielectric. Recently Huck et al. [Huck A, et al. Phys Rev Lett, 2009, 102: 246802] proved that SPPs can be in a squeezed state, and the squeezed surface plasmons can propagate in a gold waveguide. In this paper, we introduce a quantum mechanical description of the squeezed surface plasmons at first, and discuss the influence of the waveguide losses on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In Sn-Ag-Cu/Cu and Sn-Ag-Cu/Ni reaction couples, the strain rate transition from soldercontrolled ductile fracture to the IMCs-controlled brittle fracture has also been observed as strain rates increased [65,174]. Moreover, at very high strain rates, the propagation of fracture moves to the substrate side, along the Cu 3 Sn layer [175]. At high strain rates, it has been reported that short aging of around one hour can dramatically reduce the shear strength of Sn-Pb [176], Sn-Cu and Sn-Ag(-Cu) [177] solder joints.…”
Section: The Role Of Cu 6 Sn 5 In Solder Joint Integritymentioning
confidence: 96%
“…In Sn-Ag-Cu/Cu and Sn-Ag-Cu/Ni reaction couples, the strain rate transition from soldercontrolled ductile fracture to the IMCs-controlled brittle fracture has also been observed as strain rates increased [65,174]. Moreover, at very high strain rates, the propagation of fracture moves to the substrate side, along the Cu 3 Sn layer [175]. At high strain rates, it has been reported that short aging of around one hour can dramatically reduce the shear strength of Sn-Pb [176], Sn-Cu and Sn-Ag(-Cu) [177] solder joints.…”
Section: The Role Of Cu 6 Sn 5 In Solder Joint Integritymentioning
confidence: 96%
“…( 57)), we consider both attenuating and amplifying systems. Moreover, because of the quantum nature of (57) we can consider these conditions for two different kinds of SPP modes, i.e., coherent and squeezed states [29].…”
Section: B Propagation In Amplifying and Attenuating Mediamentioning
confidence: 99%
“…In Ref. [29], it is mentioned that the SPP operators, like photon operators, satisfy the Bosonic commutation relations. Therefore, we can define the coherent states of SPP as eigenvector of its annihilation operator, in accordance with the definition of the coherent states of radiation field, âR (ω)|α = α|α .…”
Section: Coherent State Of Sppmentioning
confidence: 99%
See 2 more Smart Citations